Phenolic Substances in Foods and Anticarcinogenic Properties: A Public Health Perspective. (24th June 2020) - Laganà, Pasqualina; Coniglio, Maria Anna; Fiorino, Marco; Delgado, Amélia Martins; Chammen, Nadia; Issaoui, Manel; Gambuzza, Maria E; Iommi, Candela; Soraci, Luca; Haddad, Moawiya A; Delia, Santi
Abstract: The interest in polyphenols from vegetable sources has been progressively increased because of the demonstrated correlation between their abundance in certain foods or food preparations of traditional importance and heritage, and the answer of anti-inflammatory strategies in hospitalized patients in the presence of polypehnol-rich foods (as a complementary therapy). Consequently, research involving the accessory role of polyphenols as anti-tumoral aids have been carried out with the aim of finding new additional strategies. The purpose of this paper to evaluate the role of phenolic compounds in foods with reference to health effects for human beings. The importance of these molecules has been evaluated by the health and safety perspectives in terms of: fight to cardiovascular diseases; prevention of chronic-degenerative disorders; general antioxidant properties; and anticarcinogenic features. Moreover, the role of polyphenols-rich foods as anticancer agents has been discussed with relation to two distinct "action plans" on the public hygiene level: the promotion of human health on the one side (for non-hospitalized and normal subjects), and reliable contrasting strategies in cancer patients.